OPTIMALISASI KETERAMPILAN BERBICARA DI DEPAN UMUM GURU-GURU PAUD GUGUS CEMPAKA KECAMATAN BANYUMANIK SEMARANG DENGAN METODE PELATIHAN TERBIMBING - Larasati, Larasati (SASINDO, 2014)
Early childhood teachers in Cepaka Force District of Semarang Banyumanik havethe ability to speak relatively low. Low ability to speak was revealed during groupactivities that involve host, giving a speech, and spoke convey ideas in the officialforums. Sights throwing task, passive atmosphere, and shame is the atmosphere thatroutinely occurs. The poor condition of the ability to speak directly affect the learningprocess in the classroom and the activities of the organization are often held the ECDgroup.It is the underlying researchers to conduct skills training speaking guided. Guidedtraining chosen by reason of the model is done in a structured training ranging fromthe provision of key material, duskusi understanding of the material, practices, andassistance, while Public speaking chosen with consideration of this activity is practical,contextual and everyone, especially teachers definitely need and experience.Training went well. Teachers happy and enthusiastic in practice. There is anunderstanding that early childhood teachers in Cempaka group requires intensivetraining on public speaking is. Another innovative training necessary to improvespeaking skills of early childhood teachers in the district Banyumanik cluster Cempakathis.Keywords: speaking skills, early childhood teachers, public speaking, guided exercises